Insights into microbial compositions of the respiratory tract of neonatal dairy calves in a longitudinal probiotic trial through 16S rRNA sequencing - Tan, Jia W.; Eicher, Susan D.; Kritchevsky, Janice E.; Bryan, Keith A.; Dickey, Aaron; Chitko-McKown, Carol G.; McDaneld, Tara G. (Frontiers in Microbiology, 2025)
IntroductionProbiotics are a promising intervention for modulating the microbiome and the immune system, promoting health benefits in cattle. While studies have characterized the calf lung bacterial profile with and without oral probiotics, simultaneous probiotic effects on the bacterial populations of multiple sites along the respiratory tract have not been characterized.MethodsThis study utilized the same pre-weaning diary calf group from our previous studies to characterize the bacterial populations present in the nostril and tonsil across control and treatment groups and nine sampling time points. DNA was exacted from the nostril and tonsil swabs and lung lavage fluids, and 16S ribosomal RNA gene hypervariable regions 1-3 were subsequently sequenced.ResultsTemporal variation in alpha bacterial diversity within the nostril, tonsil, and lung samples was observed, indicating distinct bacterial compositions among sampling time points. Oral probiotic treatment did not change alpha diversity in any respiratory tissue, however, spatial variability in bacterial taxa composition was observed among the three respiratory tract regions. While the majority of differentially abundant taxa in probiotic treated calves were unique to their anatomical location, a few were common to two anatomical locations and one Finegoldia amplicon sequence variant was differentially abundant in all three anatomical locations.DiscussionIn conclusion, these findings contribute to the understanding of the dynamic nature of bacterial diversity and the potential effects of probiotics within the bovine respiratory tract and provides insight for future studies of probiotics on animal health, disease prevention, and management.